Preparation and Purification of Dipeptidyl Peptidase-IV Inhibitory Peptides from Pearl Mussel Muscle - ZHANG Chuhan, CHEN Yinge, MA Ting, WENG Ling, ZHANG Lingjing, ZHANG Genfang, CAO Minjie (Shipin Kexue)
Objective: Bioactive peptides with an inhibitory effect on dipeptidyl peptidase-IV (DPP-IV) were prepared from pearl mussel muscle. Methods: Two-step enzymatic hydrolysis was adopted and enzymatic hydrolysis conditions were optimized. Fractions with in vitro DPP-IV inhibitory activity were concentrated by ultrafiltration, and purified by SuperdexTM peptide 10/300 GL gel filtration column chromatography and reverse phase-high performance liquid chromatography (RP-HPLC). DPP-IV inhibitory peptides were purified from the enzymatic hydrolysate and their amino acid sequences were identified by liquid chromatography-tandem mass spectrometry. Results: Both neutral protease and alkaline protease could effectively hydrolyze pearl mussel muscle. After concentration using a 3 kDa cut-off ultrafiltration membrane, the DPP-IV inhibition rate of the enzymatic hydrolysate reached 67.4%. After separation by gel filtration column and purification by RP-HPLC, 6 active peptides were obtained, whose sequences were FNAPAM, FIPNY, IYNPPTPF, LAMPYP, FFVVMP and LAGMP, respectively. Furthermore, the interactions between these peptides and DPP-IV were analyzed by molecular docking. Conclusion: Our present study provides a theoretical reference for the effective utilization of fish processing byproducts as raw materials for functional food production.